Implementasi Program Keluarga Harapan Dinas Sosial Kota Padang Perspektif Pemberdayaan Masyarakat - Abadi, Firman; Kohar, Wakidul Kohar (Fakultas Dakwah dan Ilmu Komunikasi, 2020)
Abtract PKH program implementation in Padang City has not been successful, because there are still poverty, malnutrition, mothers died due to childbirth, and low awareness of the community that supports the improvement of welfare. This study aims to find out the planning, implementation of the hope family program in the perspective of community empowerment. Suggestions that can be implemented are evaluating government policies on the implementation of the family of hope program and providing Value to individuals. This research states that:1. The family of hope program is generally not perfectly successful, but can contribute to the poor. 2. Family hope programs in helping the community's economy include cash assistance programs, complementary assistance to communities, school children, people with disabilities, and pregnant women. 3. The hope of the family program in its use provides support and motivation so that the community can produce and improve the economy. In the perspective of empowerment to the 3 points above from the hope family program, it has fulfilled the terms and conditions in empowering the poor in the city of Padang, the hope family program empowers the community through economic, social, spiritual. Keywords: Implementasi Program Keluarga harapan